Patient-Specific Instruments for Forearm Sarcoma Resection and Allograft Reconstruction in Children: Results in 4 Cases. (31st October 2022) - Paulmier, Amaury; Raad, Mathieu; Verhelle, Charles-Edouard; Paul, Laurent; Docquier, Pierre-Louis
Abstract : For pediatric malignant bone tumors located in the limbs, limb salvage surgery is the gold standard, but it requires adequate resection margins to avoid local recurrence. Primitive bone sarcomas of the forearm (radius or ulna) are very rare and the reconstruction remains challenging. We describe a method to ensure minimal but adequate resection bone margins with precision in four consecutive patients with primitive bone sarcomas of the forearm. During the preoperative planning, magnetic resonance imaging (MRI) was used to delineate the tumor and the tumor volume was transferred to computerized tomography (CT) by image fusion. A patient-specific instrument (PSI) was manufactured by 3D printing to allow the surgeon to perform the surgical cuts precisely according to the preoperative planning. The first PSI was used for the resection of the tumor, which adopted a unique position at the bony surface. A second PSI was intended for the cutting of the bone allograft so that it fitted perfectly with the bone defect. In all four cases, the safe margin obtained into the bone was free of tumor (R0: microscopically margin-negative resection). The functional result was very good in all four patients. This limb salvage surgical technique can be applied in forearm bone sarcoma and improves surgical precision while maintaining satisfactory local tumor control. It can also reduce the surgical time and allow a stable osteosynthesis.